The Influence of Internal Control System on The Quality of Accounting Information Systems and its Impact on the Quality of Accounting Information - Mutiara Ramadhani; Achmad Fadjar (Publikasi Indonesia, 2025)
This study aims to analyze the impact of the internal control system on the quality of accounting information systems and its effect on the quality of accounting information. The research was conducted on the Branch Delivery System of Bank Mandiri in the Asia Afrika area of Bandung. Data were collected through a questionnaire survey distributed to relevant employees. The results indicate that the internal control system has a significant positive effect on the quality of accounting information systems and the quality of accounting information. Additionally, the quality of accounting information systems contributes to improving the quality of accounting information. This study provides practical implications, suggesting that enhancing the internal control system can improve the quality of accounting information produced by the organization.